More social studies through children's literature : an integrated approach - Fredericks, Anthony D. (Englewood, CO : Teacher Ideas Press, 2000)
Presents thirty-three literature-based social studies units, each with book summaries, social studies topic areas, critical thinking questions, and activities for every grade level. Includes lists of Web sites and annotated bibliographies.
Includes bibliographical references (p. 195-206) and index.
Library Talk starred.
Reference and Research Book News.
School Library Journal.
Professional
Keywords: Children's literature -- Study and teaching (Elementary) -- United States; Language experience approach in education -- United States; Social sciences -- Study and teaching (Elementary) -- United States; Children's literature -- Study and teaching; Social sciences -- Study and teaching; Whole language